ANALISIS KETERKAITAN FUNGSIONAL WILAYAH DAN SEKTORAL PERBATASAN JAWATENGAH-JAWATIMUR DAN IMPLEMENTASINYA DALAM KERJASAMA PENGEMBANGAN WILAYAH - Mursid Zuhri (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
The main goal of this research is to describe the functional region pattern of the border of Central Java and East Java. There are four subyectives: (a) to Identify the social economic potentialities of the districts a long the border area, (b) to Identify the nodal districts a long the border area, (c) to Identify tbe factors which may form the functional region a long the Central Java and East Java Border, and ( d) to Identify tbe barrier factors which affect the district to functioning. The unit analyses of this study are all districts a long the border area of Central Java and East Java in the regional development approach. This study found that not all districts have functional region. There are three kinds of region : (a) The functional region, (b) The potential functional region, and (c) The nonfunctional region. Functional regions are distinguished by the degree to which they are integrated, or the extent of the interaction of their component. The Factor that form the functional region is that the bordering provinces see some potential strengths of the region which can be activated economically, and must be supported with infrastructures (road, bridges, transportation). The factor that makes some regions not fungtionery, is the lack of infrastructures. In fact, there is a dependent. The factor which form the dependency is the domination of the stronger functional area